POTENSI LIMBAH INDUSTRI KELAPA SAWIT DI INDONESIA - indriyati, Indriyati (Jurnal Rekayasa Lingkungan)
The status of indonesian palm oil industry in the world to be the fi rst one that built a modern palm oil industry. There is a trend of palm oil industry in the future time to be the dominan industry. On 2005 was increse to be 5.597.158 ha with CPO production about 12.451.000 ton which is spread in 20 provinces. The increasing of palm oil production give impact to solid and liquid waste potential. All the waste can be used as energy alternatif, beside that the potency of solid and liquid waste will give contribution to CO2 emission of global warming.Key words : palm oil.